Sosialisasi Kesehatan Menstruasi Bagi Remaja Perempuan di Panti Asuhan Anak Harapan Kalimantan Timur - Pasha, Tito Amellya; Khalisa, Selvi Nur; Zamima, Raysa; Khairunnisa, Rizka Tri; Mustangin, Mustangin (TAAWUN, 2023)
Menstruation is a common thing that happens to women, but during menstruation, women feel pain and uncomfortable conditions, especially teenagers who have just experienced menstruation. Lack of knowledge about menstrual cycles and improper handling can affect adolescent female activityTherefore, it is necessary to increase knowledge for adolescent girls related to menstruation and menstrual health management. This community service program is carried out through socialization activities for women, especially adolescents. The target of this program is foster children at the Harapan Children's Orphanage (Panti Sosial Asuhan Anak Harapan/PSAAH). Activities are carried out with preparatory stages in the form of coordination with PSAAH leaders and establishing mutual agreements for program implementation. Stages of preparing learning tools for socialization in the form of modules and pre-test and post-test devices. The stages of implementing activities are in the form of implementing socialization activities. Socialization is carried out using the lecture method for the delivery of material related to menstruation and menstrual health. The result of dedication is the high enthusiasm seen from the activeness of socialization participants. The results of this service activity are beneficial for adolescent girls in PSAAH, namely, women gain knowledge related to menstruation and healthy menstrual management. The results of the service also showed that there was a 95% change in knowledge related to menstruation and menstrual health. This community service program has a positive impact, namely changing the knowledge of foster children, especially adolescent girls in PSAAH East Kalimantan.